Measuring trade-offs among criteria in a balanced scorecard framework: possible contributions from the multiple criteria decision analysis research field - Ferreira, Fernando A. F. (Journal of Business Economics and Management, 2013)
Claimed by the Harvard Business Review as one of the main innovations of recent decades in management systems, the Balanced Scorecard (BSC) has been widely studied and applied in different management contexts. However, despite recent progress and its undeniable merit, the BSC has its own shortcomings. As reported in the literature, it seems generally agreed that the way compensations between criteria within a BSC framework are calculated remains an open issue. Thus, one of the contributions of this study is to augment the theoretical discussion on the potentialities of the multiple criteria decision analysis (MCDA) approach to bring simplicity and transparency to the calculation of compensations (i.e. trade-offs) among evaluation criteria within a BSC framework. It seems important to underline that this paper builds on previous work and is not empirical research. However, it aims to extend the discussion to other (new) measurement contexts. We believe that the development and promotion of the integrated use of MCDA tools in BSC applications to measure trade-offs among evaluation criteria in the BSC framework can be a key factor in ensuring more successful implementations and uses of the BSC within firms.